Consuming pleasures : active audiences and serial fictions from Dickens to soap opera - Hayward, Jennifer Poole (University Press of Kentucky, 1997)
""To be continued... "" Whether these words fall at a season-ending episode of Star Trek or a TV commercial flirtation between coffee-loving neighbors, true fans find them impossible to resist. Ever since the 1830's, when Charles Dickens's Pickwick Papers enticed a mass market for fiction, the serial has been a popular means of snaring avid audiences. Jennifer Hayward establishes serial fiction as a distinct genre -- one defined by the activities of its audience rather than by the formal qualities of the text. Ranging from installment novels, mysteries, and detective fiction of the 1800's.
Keywords: Television series -- History and criticism.; Serialized fiction -- History and criticism.; Authors and readers -- History.; Séries télévisées -- Histoire et critique.; Roman-feuilleton -- Histoire et critique.; Écrivains et lecteurs -- Histoire.; PERFORMING ARTS -- Television -- Reference.; Authors and readers; Serialized fiction; Television series; Fernsehserie; Geschichte; Fortsetzungsroman; Seriewerken.; Televisieseries.; Engels.; Strips.; Englisch.; Electronic book.; Criticism, interpretation, etc.; History